Mrs Draga Gelt performs rhymes and songs in Slovenian for the Australian Children's folklore collection - Gelt, Draga; Davey, Gwenda, 1932- (1979)
Folkloric recording. The Collection consists of traditional songs, music, rhymes and stories in several languages for young children selected by Gwenda Davey from original field recordings located at Museum Victoria.
Rhymes and singing: Five Rats. Singing: Ring a Rosy. Rhymes: Tiki Miki -- Three kings stole a cow. Singing: Red cherries -- White lily -- Little Matthias.
Recorded in Melbourne, Victoria on 11 September 1979.
Digital master available
In Slovenian. Items accompanied by translation and description in English.
Keywords: Children's songs -- Australia; Children's poetry; Folk poetry, Slovenian -- Australia; Folk songs, Slovenian -- Australia; Slovenes -- Australia -- Folklore